A Stastistical quality control analysis on Alcos Global Corporation - Herrin, Mark Andrew; Reyes, Jose Ricardo J.; Sabado, Jorge D.; Tiongson, Ciselle Myn C. (College of Engineering, 2001)
lcos Global Corporaton, formerly known as TOPY Industries Inc., is a 13 year-old corporation with plant at Bagumbayan, Quezon City. AGC manufactures plastic containers using injection molding and injection blow molding. Through thorough Problem Analysis, with the aid of problem identification tools such as Cause and Effect Diagrams, Pareto Chart and Histograms, the three problems, one attribute problem and two variable problems, on the manufacture of the 750 mL AVON Herbal Care bottles are identified. These are the Presence of Black Spots (attribute), the Excessive Product Volume, and the High Variance of Product Weight (variables). Before proceeding to further analysis, Test for Data Randomness, Goodness of Fit Test, Analysis of Variance (ANOVA), and Duncan's Multiple Range Test (DMRT), are utilized to verify the randomness of data, to determine the the distribution of data, to determine the significant factor(s), and to identify the specific factor that affects the variable, respectively. Statistical Process Control (SPC), through the use of appropriate control charts, is utilized for each problem. Process Capability Analysis is then performed on the problems on volume and weight. These analyses show that the process is out-of-control with respect to the manufacture of products with the correct volume, and is in-control with respect to the other two problems. Also, with the process capability indices below the value of one: 0.01 process capability index for product volume and 0.4959 process capability index for product weight, the process is inadequate and corrective action must begin immediately.